1988
DOI: 10.1177/0022427888025002003
|View full text |Cite
|
Sign up to set email alerts
|

The National Punishment Survey and Public Policy Consequences

Abstract: Research into the criminal justice policy formation process has made it clear that public preferences are important influences. While public preferences about punishment are often strong and well-articulated, they are largely unconstrained by the consequences associated with those choices. This study examines these policy issues as they relate to a recent national survey of public attitudes concerning punishment for criminal offenses. The potential policy consequences of the preferences expressed in the survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…While some research showed that the public holds rehabilitative ideals for some offenses (Cullen, Skovron, Scott, & Burton, 1990;McCorkle, 1993), many studies showed that members of the public hold fairly punitive values (Payne, Gainey, Triplett, & Danner, 2003;Zimmerman, Van Alstyne, & Dunn, 1988). Failing to support rehabilitative ideals may simply result from a general reluctance to support rehabilitative ideals for any type of offense.…”
Section: Discussionmentioning
confidence: 99%
“…While some research showed that the public holds rehabilitative ideals for some offenses (Cullen, Skovron, Scott, & Burton, 1990;McCorkle, 1993), many studies showed that members of the public hold fairly punitive values (Payne, Gainey, Triplett, & Danner, 2003;Zimmerman, Van Alstyne, & Dunn, 1988). Failing to support rehabilitative ideals may simply result from a general reluctance to support rehabilitative ideals for any type of offense.…”
Section: Discussionmentioning
confidence: 99%
“…Though some research showed support for community-based sanctions (see Brown & Elrod, 1995;Payne & Gainey, 1999), other research showed that the public preferred relatively long sentences for convicted offenders (Zimmerman, Van Alstyne, & Dunn, 1988). A quote from McCorkle (1993, p. 251) reconciles these seemingly disparate findings as far as punishment preferences are concerned: ''[The public's] priorities seem clear: Incarcerate first, then rehabilitate if possible.''…”
Section: Punishment and Sentencing Attitudesmentioning
confidence: 99%
“…Of course lengthy sentences can be costly. Research by Zimmerman et al (1988) found that if the public's preferred sanctions (from the 1987 U.S. National Punishment Survey) were given to a cohort of offenders convicted in New York, the cost of punishment would increase by 2.5 billion dollars in New York alone.…”
Section: Punishment and Sentencing Attitudesmentioning
confidence: 99%
“…First, research has shown almost universally that an individual's estimation of the seriousness of the offense plays a central role in his or her decision about appropriate punishments. Specific offense characteristics that generally have significant effects on decision making include (1) the amount of harm inflicted on a victim (Applegate et al, 1996;Rossi, Simpson, & Miller, 1985;Turner, Cullen, Sundt, & Applegate, 1997), (2) the dollar amount of property stolen (Applegate et al, 1996;Hamilton & Rytina, 1980;Rossi et al, 1985;Stalans & Diamond, 1990;Turner et al, 1997), and (3) whether or not the offender was carrying and/or used a weapon (Applegate et al, 1996;Turner et al, 1997;Zimmerman, Van Alstyne, & Dunn, 1988).…”
Section: Perceptions Of Sentencingmentioning
confidence: 99%